Usefulness of determining a method in the science of canon law - GAŁKOWSKI, TOMASZ (Prawo Kanoniczne, 2017)
The article poses the question concerning the usefulness of determining a method used in research on canon law, whose perspective is not unambiguous. The author points out that in the discussion about the method one does not always distinguish ontological issues (what the canon law is) and epistemological ones (how to study it) from the problem of legal phenomena, that is truths and occurrences connected with the existence and effects of law. It allows to select a study method of legal phenomena which depends on the research purpose and the properties of the object (aspect), which in canon law must take into consideration its theological perspective.